Pendampingan Pemanfaatan Secang Sebagai Pewarna Ecoprint untuk Menghasilkan Warna Burn Coral Red di CV. Rasyid - Widyastuti Widyastuti; Wibowo, Eko Ari; Dicasani, Alifta; Betanursanti, Ida (Lembaga Pengembangan Kinerja Dosen, 2025)
CV. Rasyid is a business unit specializing in the production of ecoprints. Currently, one of the most sought-after clothing colors by consumers is burnt coral red. However, CV. Rasyid has been unable to meet this demand due to challenges in the production process, specifically the deterioration of the color during the fixation stage. To address this issue, the community service team from the Industrial Engineering Study Program at Muhammadiyah University of Gombong (Unimugo) provided facilitation and support. The program aims to equip participants with the knowledge and skills needed to produce burnt coral red for ecoprints using secang dye. The activities include preparation, implementation, monitoring, and evaluation. The implementation process was conducted with guidance on color extraction, mordanting, design printing, and fixation. Monitoring results indicate that CV. Rasyid successfully carried out the burnt coral red ecoprint production process independently without significant issues. While the colors produced may vary slightly, this is not a concern, as such variations are a unique characteristic of ecoprint products.